Nanoemulsions for food applications: development and characterization - Silva, Hélder D. (2012)
The application of nanotechnology to food, medical and pharmaceutical industries has received great attention from the scientific community. Driven by the increasing consumers’ demand for healthier and safer food products and the need for edible systems able to encapsulate, protect, and release functional compounds, researchers are currently focusing their efforts in nanotechnology to address issues relevant to food and nutrition. Nanoemulsion technology is particularly suited for the fabrication of encapsulating systems for functional compounds as it prevents their degradation and improves their bioavailability. This review focuses on nanoemulsions and provides an overview of the production methods, materials used (solvents, emulsifiers and functional ingredients) and of the current analytical techniques that can be used for the identification and characterization of nanoemulsions. Finally, nanotechnological applications in foods currently marketed are reported.